2018
DOI: 10.1017/s0021932018000093
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Childhood Obesity and Undernutrition Among Urban School Children in Bangladesh

Abstract: SummaryDespite the ongoing problems of undernutrition and infectious disease, obesity and overweight have become a major problem in developing countries, including Bangladesh. This cross-sectional study was undertaken to determine the prevalence of obesity, overweight and underweight among school children aged 6-12 years in Bangladesh. The study was conducted from June 2012 to May 2013 and the study sample comprised 1768 children (980 boys; 788 girls) from eight purposively selected schools in different areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
0
10
0
2
Order By: Relevance
“…These barriers need to be addressed to increase children's PA and, thereby, both stem the rising tide of overweight and obesity among school children in Bangladesh and contribute to overall health throughout the population [27,28]. In previous studies addressing urban Bangladeshi school children, researchers reported a high prevalence of overweight and obesity [29,30] and identified sedentary activities as a risk factor [23]. Researchers also reported that regular PA can protect against overweight and obesity [31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These barriers need to be addressed to increase children's PA and, thereby, both stem the rising tide of overweight and obesity among school children in Bangladesh and contribute to overall health throughout the population [27,28]. In previous studies addressing urban Bangladeshi school children, researchers reported a high prevalence of overweight and obesity [29,30] and identified sedentary activities as a risk factor [23]. Researchers also reported that regular PA can protect against overweight and obesity [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Strong PA curricula in schools may help inculcate lifelong habits of PA and reduce the risk of future diseases and disabilities in the Bangladeshi population. In view of the rise in overweight and obesity among children in urban areas [29,30] and the rise in deaths due to non-communicable diseases in Bangladesh [48], it is important that strong steps be taken to improve the opportunities for PA for school-aged children.…”
Section: Plos Onementioning
confidence: 99%
“…and overweight or obesity of 25% [12]. Another study on 6-12 years old school children from Dhaka reported that prevalence of underweight was 22.1% in poorer children versus 11.2% in rich children [13]. Another country wide study involving 10,135 students from 6 to 15 years reported that underweight children were 19.2% in rural schools versus 16.1% in urban schools [14].…”
Section: Discussionmentioning
confidence: 99%
“…Here, Z_(1-α/2) = normal standard deviation (Type 1 error of 5% (p<0.05) is 1.96, p=expected proportion of the population based on previous analysis of 1,768 children (980 boys; 788 girls) from eight schools selected for purpose in various areas of Dhaka City, which is 0.05 (5.0 percent). 17 d= absolute error, or precision set to 0.05. This proposed study had at least 77 subjects according to formula.…”
Section: Sample Size Determination and Samplingmentioning
confidence: 99%